Mode I+II Fatigue Crack Growth Delay by Stop-Holes - Pavlou,Dimitrios G. (2018)
ABSTRACT: The technique of retarding the growth of fatigue cracks by drilling holes on the crack tip is well known. Most of the research works on this subject are limited to fatigue cracks subjected to mode I loading conditions. In the present work the fatigue crack growth retardation by stop-holes of cracks under mode I+II loading is investigated. The proposed approximate solution is based on the implementation of a mixed-mode fatigue crack growth model and a multiaxial high cycle fatigue criterion. Numerical results for mode I+II fatigue crack growth retardation on Al-2024 thin plate are derived and the effect of the crack inclination angle, as well as the diameter of the stop-hole, are discussed and commented.